Exoplanetas: classificação, habitabilidade e métodos de detecção - Medeiros, Eder Campos (2019)
This work results from a bibliographical survey on the subject of Exoplanets. In view of this, it was sought in each chapter to describe the relevant issues within astronomy about the discoveries, beginning in antiquity when the man began to raise his head to heaven and then see what in uences the natural events made in their lives . The more we discovered, the more questioning they made. From what they discovered, they were doing great advances to science. And these advances, of course, resulted in methods for scientists to make the rst discoveries of planets, rst within our solar system and subse- quently to other solar systems despite the great astronomical distances. And since then the studies for these new planets began, analyzing them and classising them according to the planetary parameters of our solar system. And so be able to con rm if there is any planet with the characteristics of the earth and if it is habitable, but for this planet to be habitable has to orbit a star of the spectral class F, G, K and M and also be within an area called habitable zone. Where if I marry the planet is outside this area, it would be impossible for the development of life, as we know it.